Thermococcus kodakarensis as a Host for Gene Expression and Protein Secretion - Takemasa, Ryo (American Society for Microbiology (ASM), 2011)
Taking advantage of the gene manipulation system developed in Thermococcus kodakarensis, here, we developed a system for gene expression and efficient protein secretion using this hyperthermophilic archaeon as a host cell. DNA fragments encoding the C-terminal domain of chitinase (ChiAΔ4), which exhibits endochitinase activity, and the putative signal sequence of a subtilisin-like protease (TK1675) were fused and positioned under the control of the strong constitutive promoter of the cell surface glycoprotein gene. This gene cassette was introduced into T. kodakarensis, and secretion of the ChiAΔ4 protein was examined. ChiAΔ4 was found exclusively in the culture supernatant and was not detected in the soluble and membrane fractions of the cell extract. The signal peptide was specifically cleaved at the C-terminal peptide bond following the Ala-Ser-Ala sequence. Efficient secretion of the orotidine-5′-monophosphate decarboxylase protein was also achieved with the same strategy. We next individually overexpressed two genes (TK1675 and TK1689) encoding proteases with putative signal sequences. By comparing protein degradation activities in the host cells and transformants in both solid and liquid media, as well as measuring peptidase activity using synthetic peptide substrates, we observed dramatic increases in protein degradation activity in the two transformants. This study displays an initial demonstration of cell engineering in hyperthermophiles.